Relationship of the bovine IGF1, TG, DGAT1 and MYF5 genes to meat colour, tenderness and cooking loss - ARDICLI, S.; SAMLI, H.; DINCEL, D.; EKIZ, B.; YALCINTAN, H.; VATANSEVER, B.; BALCI, F. (Journal of the Hellenic Veterinary Medical Society, 2018)
Bovine insulin-like growth factor 1 (IGF1), thyroglobulin (TG), diacylglycerol-O-acyltransferase 1 (DGAT1) and myogenic factor 5 (MYF5) genes play an important role in the physiology of lipid and muscle metabolism and are therefore considered as candidate genes for meat production traits in farm animals. The objectives of this study were to investigate single nucleotide polymorphisms (SNPs) in IGF1, TG, DGAT1 and MYF5 genes and to evaluate whether these polymorphisms affected meat colour, tenderness and cooking loss in Holstein cattle. Initially, the SNPs were detected by polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) method. Meat samples (N= 50) derived from M. longissimus thoracis et lumborum (LTL) were used in the current study. Significant differences in variations of meat colour parameters were observed at 24 hours post-mortem. IGF1 was associated with colour parameters of a* and chroma values. In addition, effects of TG were statistically significant on L* and a* values, while, effects of MYF5 were significant on a* value. There was no association of the tested SNPs with meat pH, tenderness and cooking loss. The results presented here may give the valuable information for improving meat colour in cattle.